Evolution and Comparative Genomics of F33:A−:B− Plasmids Carrying blaCTX-M-55 or blaCTX-M-65 in Escherichia coli and Klebsiella pneumoniae Isolated from Animals, Food Products, and Humans in China - Jing Wang (American Society for Microbiology, 2018)
ABSTRACT To understand the underlying evolution process of F33:A−:B− plasmids among Enterobacteriaceae isolates of various origins in China, the complete sequences of 17 blaCTX-M-harboring F33:A−:B− plasmids obtained from Escherichia coli and Klebsiella pneumoniae isolates from different sources (animals, animal-derived food, and human clinics) in China were determined. F33:A−:B− plasmids shared similar plasmid backbones comprising replication, leading, and conjugative transfer regions and differed by the numbers of repeats in yddA and traD and by the presence of group II intron, except that pHNAH9 lacked a large segment of the leading and transfer regions. The variable regions of F33:A−B− plasmids were distinct and were inserted downstream of the addiction system pemI/pemK, identified as the integration hot spot among F33:A−B− plasmids. The variable region contained resistance genes and mobile elements or contained segments from other types of plasmids, such as IncI1, IncN1, and IncX1. Three plasmids encoding CTX-M-65 were very similar to our previously described pHN7A8 plasmid. Four CTX-M-55-producing plasmids contained multidrug resistance regions related to that of F2:A−B− plasmid pHK23a from Hong Kong. Five plasmids with IncN and/or IncX replication regions and IncI1-backbone fragments had variable regions related to those of pE80 and p42-2. The remaining five plasmids with IncN replicons and an IncI1 segment also possessed closely related variable regions. The diversity in variable regions was presumably associated with rearrangements, insertions, and/or deletions mediated by mobile elements, such as IS26 and IS1294. IMPORTANCE Worldwide spread of antibiotic resistance genes among Enterobacteriaceae isolates is of great concern. F33:A−:B− plasmids are important vectors of resistance genes, such as blaCTX-M-55/-65, blaNDM-1, fosA3, and rmtB, among E. coli isolates from various sources in China. We determined and compared the complete sequences of 17 F33:A−:B− plasmids from various sources. These plasmids appear to have evolved from the same ancestor by mobile element-mediated rearrangement, acquisition, and/or loss of resistance modules and similar IncN1, IncI1, and/or IncX1 plasmid backbone segments. Our findings highlight the evolutionary potential of F33:A−:B− plasmids as efficient vectors to capture and diffuse clinically relevant resistance genes.